Manajemen Program Pengajian Muhammadiyah dalam Peningkatan Mutu Guru Pendidikan Agama Islam di SMP Muhammadiyah 7 Medan Tahun 2024 - Siti Khairiah; Ali Imran Sinaga (EduInovasi: Journal of Basic Educational Studies, 2024)
Recitation is a means of knowledge that can increase motivation, shape character and obey Allah. This recitation has a positive impact and has an important role in creating thought patterns, attitudes and behavior that are in accordance with Islamic teachings. Apart from that, teachers and the community involved in it can feel the benefits of this activity as a means of moral development and increasing Islamic knowledge to improve the quality of the listeners. This research uses a descriptive qualitative method with data collection techniques in the form of observation, interviews and documentation of teachers. This research aims to improve the quality of teachers at Muhammadiyah Middle School 7 Medan, to find out how the recitation process takes place and what factors support and inhibit the recitation process.